Antiherpes simplex virus type 2 activity of the antimicrobial peptide subtilosin - Quintana, Verónica Mara (2014)
In the present study we evaluated the antiviral activity of subtilosin, a cyclical peptide isolated from Bacillus amyloliquefaciens, against herpes simplex virus type 2 (HSV-2) in cell cultures and we investigated subtilosin mode of action. We determined, using a virus yield inhibition assay, that non cytotoxic concentrations of subtilosin inhibit HSV-2 replication in Vero cell cultures. Subtilosin strongly inhibited extracellular and total virus production even when it was added at 8 h post-infection indicating that not only virus release but also viral particle formation is impeded by the antiviral peptide. Although viral glycoprotein gD level of expression is not affected by the bacteriocin, an altered pattern of gD intracellular localization was detected by immunofluorescence assay in subtilosin treated culture. On the other hand, at high concentrations subtilosin displays virucidal action.